2013
DOI: 10.1051/0004-6361/201322808
|View full text |Cite
|
Sign up to set email alerts
|

Kelvin-Helmholtz instability of twisted magnetic flux tubes in the solar wind

Abstract: Context. Tangential velocity discontinuity near the boundaries of solar wind magnetic flux tubes results in Kelvin-Helmholtz instability, which might contribute to solar wind turbulence. While the axial magnetic field stabilizes the instability, a small twist in the magnetic field may allow sub-Alfvénic motions to be unstable. Aims. We aim to study the Kelvin-Helmholtz instability of twisted magnetic flux tubes in the solar wind with different configurations of the external magnetic field. Methods. We use magn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 43 publications
2
57
0
2
Order By: Relevance
“…Therefore, the gradient of the pressure perturbation is retained in the momentum equation, while the time derivative of density perturbations is neglected in the continuity equation (Chandrasekhar 1961). After straightforward calculations, the total (thermal + magnetic) pressure perturbations are governed by the Bessel equation (Goossens et al 1992;Zaqarashvili et al 2014Zaqarashvili et al , 2015 which has a solution in terms of Bessel functions. The continuity of the Lagrangian total pressure and displacement results in the dispersion equation where ω is the angular frequency, w Ai and w Ae are the Alfvén frequencies inside and outside the tube respectively, m is the azimuthal wave number, k z is the longitudinal wavenumber, and r i and r e are the densities inside and outside the tube, respectively.…”
Section: Khi: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the gradient of the pressure perturbation is retained in the momentum equation, while the time derivative of density perturbations is neglected in the continuity equation (Chandrasekhar 1961). After straightforward calculations, the total (thermal + magnetic) pressure perturbations are governed by the Bessel equation (Goossens et al 1992;Zaqarashvili et al 2014Zaqarashvili et al , 2015 which has a solution in terms of Bessel functions. The continuity of the Lagrangian total pressure and displacement results in the dispersion equation where ω is the angular frequency, w Ai and w Ae are the Alfvén frequencies inside and outside the tube respectively, m is the azimuthal wave number, k z is the longitudinal wavenumber, and r i and r e are the densities inside and outside the tube, respectively.…”
Section: Khi: Theorymentioning
confidence: 99%
“…The continuity of the Lagrangian total pressure and displacement results in the dispersion equation where ω is the angular frequency, w Ai and w Ae are the Alfvén frequencies inside and outside the tube respectively, m is the azimuthal wave number, k z is the longitudinal wavenumber, and r i and r e are the densities inside and outside the tube, respectively. Furthermore, (see Zaqarashvili et al 2014). The dispersion relation (1) is a transcendental equation for the complex wave frequency, ω, whose imaginary part indicates an instability process in the system, in particular, the growth rate of unstable harmonics.…”
Section: Khi: Theorymentioning
confidence: 99%
“…For the particular case of turbulent plumes in prominences, Soler et al (2012) concluded that sub-Alfvénic flow velocities can trigger the KH instability thanks to the ion-neutral coupling. Zaqarashvili, Vörös & Zhelyazkov (2014a) in exploring the KH instability of twisted cylindrical magnetic flux tubes in the solar wind have obtained that twisted magnetic flux tubes can be unstable to KH instability when they move with regard to the solar wind stream. It was found also that the external axial magnetic field stabilizes KH instability, therefore, the tubes moving along Parker spiral are unstable only for super-Alfvńic motions.…”
Section: Waves and Instabilities In Twisted Solar Magnetic Structuresmentioning
confidence: 99%
“…Dispersion relations of MHD waves propagating on cylindrical untwisted and twisted plasma jets are generally well-known and here we will only give their final form-their derivation the reader can see in Zhelyazkov 2012a; Zhelyazkov & Zaqarashvily 2012;Zaqarashvili et al 2014 and references therein. We recall that all perturbed quantities associated with the waves are proportional to exp[−i(ωt − mφ − k z z)], where ω is the wave angular frequency, m the azimuthal wave mode number, and k z the axial wavenumber (as usual, we assume that waves propagate in z direction).…”
Section: Introductionmentioning
confidence: 99%
“…As we will demonstrate shortly, the kink mode can become unstable against the KH instability. As one can expect, the dispersion relation of MHD modes propagating on a moving twisted flux tube is more complicated and has the form (Zhelyazkov & Zaqarashvily 2012;Zaqarashvili et al 2014)…”
Section: Introductionmentioning
confidence: 99%